Caseous Calcification of the Mitral Annulus: A Rare Cause of Intracardiac Mass - Anxo Martinez-de-Alegria; Jose Rubio-Alvarez; Sandra Baleato-Gonzalez (Case Reports in Radiology)
Caseous calcification of the mitral annulus is a rare form of periannular calcification with a mass-like appearance, that has to be in the differential of the cardiologist and radiologist. It classically looks like a round or semilunar hyperdense mass with an even denser peripheral rim, located in the posterior mitral annulus and having in general no clinical significance.